The impact of black carbon (BC) on mode-specific galvanic skin response (GSR) as a measure of stress in urban environments - Yang, X; Orjuela, JP; McCoy, E; Vich, G; Anaya-Boig, E; Avila-Palencia, I; Brand, C; Carrasco-Turigas, G; Dons, E; Gerike, R; Göetschi, T; Nieuwenhuijsen, M; et al. (Elsevier, 2022)
Previous research has shown that walking and cycling could help alleviate stress in cities, however there is poor knowledge on how specific microenvironmental conditions encountered during daily journeys may lead to varying degrees of stress experienced at that moment. We use objectively measured data and a robust causal inference framework to address this gap. Using a Bayesian Doubly Robust (BDR) approach, we find that black carbon exposure statistically significantly increases stress, as measured by Galvanic Skin Response (GSR), while cycling and while walking. Augmented Outcome Regression (AOR) models indicate that greenspace exposure and the presence of walking or cycling infrastructure could reduce stress. None of these effects are statistically significant for people in motorized transport. These findings add to a growing evidence-base on health benefits of policies aimed at decreasing air pollution, improving active travel infrastructure and increasing greenspace in cities.